New Insights into an Old Problem: Increasing Medical Complexity of Patients with Active Tuberculosis in California. (4th October 2017) - Vaisman, Alon; Barry, Pennan; Flood, Jennifer
Abstract: Background: Although the number of patients with active tuberculosis (TB) has decreased in the last 25 years, it has been noted that the complexity of these patients has increased. However, this complexity and its components have never been quantified or defined. We therefore aim to describe the complexity of patients with active TB in California during 1993–2016. Methods: We analyzed data on patient comorbidities, clinical features, and demographics from the California Department of Public Health TB Registry. All adult patients who were alive at the time of TB diagnosis in California during 1993–2016 were included in the analyses. Factors deemed by an expert panel to increase complexity (i.e., increased resources or expertise requirement for successful management) were analyzed and included the following: age >75 years, HIV infection, multi-drug resistance (MDR), and extrapulmonary TB disease. Information on other comorbidities became available starting in 2010 which we analyzed as a comorbidity variable (defined as having either end-stage renal disease, diabetes, or immunosuppression). We performed linear regression to examine whether the annual proportion of such complex patients increased over time. Results: Among the 67, 512 patients analyzed, the proportion of patients with extrapulmonary disease, age >75 years, or MDR-TB each increased over the study period ( P < 0.001) while the proportion of patients with HIV decreased. Furthermore, the proportion of patients with at least one factor increased, rising from 37.5% to 45.3% from 1993 to 2016 (figure). With the addition of comorbidity to our definition of complexity, we found the same trend in increased complexity ( P < 0.001) over the period 2010 - 2016. Conclusion: In this first, of which we are aware, description of complexity in the setting of TB, we found that the complexity of patients with active TB has risen over the last 25 years in California. These findings suggest that despite the overall decline in active TB cases, effective management of more complex patients may require additional attention and resource investment. Disclosures: All authors: No reported disclosures.